Churchill Livingstone's dictionary of sport and exercise science and medicine - 4 0 16; Jennett, Sheila; 5 (Edinburgh : Churchill Livingstone Elsevier, 2008)
This dictionary provides definitions and short accounts of terms used and techniques employed in the study and practical application of the relevant anatomy, physiology, biomechanics and psychology, and of commonly associated medical problems and treatments.
Includes bibliographical references (p. 481-486)
Keywords: 2 -- 0; 6; English. -- Sports Medicine;Sports medicine -- 20 -- Dictionary;Dictionaries.; 20; 2